International Consumption Risk Sharing with Incomplete Goods and Asset Markets - Sven Blank (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Perfect consumption risk sharing requires both, frictionless goods as well as frictionless financial market integration. This project aims at analyzing the consequences of both type of frictions for the allocation of risk across countries in a unified framework. To this end, the theoretical model by Ghironi and Melitz (2005) is extended to allow for international trade in equities. This setup incorporates impediments to international trade in goods and assets. Impulse responses show that the degree of financial market integration and the time horizon considered, substantially alter the extent of consumption risk sharing depending on the nature of the underlying shock.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F32; F42; 330; International portfolio choice; consumption risk sharing; trade frictions; financial market frictions